Acute Generalized Pustular Psoriasis Developed Resistance to Adalimumab Was Successfully Treated with Narrowband Ultraviolet B and Acitretin: A Case Report - Yang X; Wang J; Wang H; Kong M; Chen Q (Dove Medical Press, 2022)
Xianjie Yang,* Juan Wang,* Huan Wang, Minmin Kong, Qiquann Chen Department of Dermatology, Southwest Hospital, Army Medical University, Chongqing, People's Republic of China*These authors contributed equally to this workCorrespondence: Qiquann Chen, Email chenqq0548@163.comAbstract: Acute generalized pustular psoriasis (GPP) is a severe but rare variant of psoriasis, characterized by an acute eruption of extensive erythema with numerous non-follicular pustules. In rare cases, local pustular psoriasis like acrodermatitis continua of Hallopeau (ACH) may progress into acute GPP if improperly treated. ACH and GPP are rare in the clinic and their treatment is more complex and often treatment-resistant compared to psoriasis vulgaris (PV). A variety of anti-psoriasis biologics emerging in recent years have been reported for the treatment of ACH and acute GPP. Biologics is considered to be an upgraded treatment option for traditional anti-psoriasis agents. But there are few reports of GPP patients developing resistance to biologics, or what if biologics fails. Herein, we report a case of acute GPP that developed from ACH, initially responded extremely well to adalimumab, but the treatment failed when the patient treated with the drug again, which is thought to have developed resistance to adalimumab, finally successfully treated with narrowband ultraviolet B (NB-UVB) and acitretin.Keywords: acute generalized pustular psoriasis, acrodermatitis continua of hallopeau, adalimumab, narrowband ultraviolet B, acitretin